2022
DOI: 10.7554/elife.77672
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-specific responses of hKv7.4 and hKv7.5 channels to polyunsaturated fatty acids reveal an unconventional modulatory site and mechanism

Abstract: The KV7.4 and KV7.5 subtypes of voltage-gated potassium channels play a role in important physiological processes such as sound amplification in the cochlea and adjusting vascular smooth muscle tone. Therefore, the mechanisms that regulate KV7.4 and KV7.5 channel function are of interest. Here, we study the effect of polyunsaturated fatty acids (PUFAs) on human KV7.4 and KV7.5 channels expressed in Xenopus oocytes. We report that PUFAs facilitate activation of hKV7.5 by shifting the V50 of the conductance vers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…This state of affairs contrasts with the effects of a high concentration of docosahexaenoic acid (Figure 5), which was shown to directly activate KCNQ5 channels through electrostatic interactions with positively charged gating charges in the upper half of the voltage-sensing domain. 34…”
Section: Resultsmentioning
confidence: 99%
“…This state of affairs contrasts with the effects of a high concentration of docosahexaenoic acid (Figure 5), which was shown to directly activate KCNQ5 channels through electrostatic interactions with positively charged gating charges in the upper half of the voltage-sensing domain. 34…”
Section: Resultsmentioning
confidence: 99%
“…Lipid peroxidation upon GPX4 inhibition is accompanied by the flow of Cl - across the plasma membrane, which could be mediated by Cl - channels. Whether Cl - channels are activated directly or indirectly by the lipid ROS is currently unclear, but fenestration exists within protein channels and channels could be opened by PUFA oxidation 43,44 . Furthermore, the flow of Cl - also influences the membrane potential, which changes during ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…CBD and other phytocannabinoids are meroterpenoids, whereas endocannabinoids are structurally similar to polyunsaturated fatty acids (PUFAs), another class of lipid that has been shown to modulate hK V 7 channels. Our laboratory has previously shown that the negatively charged head groups of polyunsaturated fatty acids and endocannabinoids form interactions with positively charged residues in the voltage‐sensing domain and pore domain of hK V 7.1 channels (Hiniesto‐Iñigo et al, 2023; Yazdi et al, 2021), while polyunsaturated fatty acids interact with other positively charged residues in hK V 7.4 (Frampton et al, 2022). CBD lacks charged moieties and as a result remains submerged in the lipid bilayer where it is unable to make the same interactions that polyunsaturated fatty acids and endocannabinoids make with channels.…”
Section: Discussionmentioning
confidence: 99%